Penegakan Hukum Yang Ditunjukan Untuk Anak Disabilitas Yang Ditelantarkan - Muhammad Aryaduta Panatayudha (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Children are a form of gift and trust from God. Every child, without exception, has value and dignity as a human being. Including children with disabilities, who are also obliged to receive protection from family, parents, law and government, just like other children. Children with disabilities sometimes do not feel fully accepted in their environment, especially their parents, and some families feel that children with special needs are a disgrace. This research was conducted using normative legal methods. To collect data, the author applied several approaches, including the case approach, statutory approach, and comparative approach. Sources of research data come from literature, including books, journals, articles, legal studies, and regulations relevant to the research topic. Regulations regarding the rights of persons with disabilities have an impact on other regulations that exist under them. Based on Law no. 39 of 1990 concerning Human Rights, Article 5 (3) confirms that every individual from a group considered vulnerable has the right to special protection and to be treated equally before the law. Constitution no. 8 of 2011 concerning Disabilities sets out the rights that persons with disabilities should receive to ensure their equal rights. In the regulations, the term